Claiming Space for Australian Women’s Writing
XV, 353 p.
Keywords: This volume explores the subterfuges, strategies, and choices that Australian women writers have navigated in order to challenge patriarchal stereotypes and assert themselves as writers of substance. Contextualized within the pioneering efforts of white, Aboriginal, and immigrant Australian women in initiating an alternative literary tradition, the text captures a wide range of multiracial Australian women authors’ insightful reflections on crucial issues such as war and silent mourning, emergence of a Australian national heroine, racial purity and Aboriginal motherhood, communism and activism, feminist rivalry, sexual transgressions, autobiography and art of letter writing, city space and female subjectivity, lesbianism, gender implications of spatial categories, placement and displacement, dwelling and travel, location and dislocation and female body politics. Claiming Space for Australian Women’s Writing tracks Australian women authors’ varied journeys across cultural, political and racial borders in the canter of contemporary political discourse.